Solid-waste-based early-strength curing agent and preparation method thereof

By using mixed preparation of slag powder, fly ash and calcium carbide slag combined with alkali exciter, the problems of high energy consumption and short curing efficiency of sludge curing agent are solved, and the efficient curing and stability of sludge is achieved, and the sludge is improved, which meets the sludge strength and environmental protection requirements.

CN119118542APending Publication Date: 2024-12-13LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411255385.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The use of a large amount of cement in the existing sludge curing agent leads to high energy consumption, and low-dose cement curing agent cannot guarantee the stability and strength of the sludge, and the curing efficiency release cycle is short.

Method used

Slag powder, fly ash and calcium carbide slag as main components, combined with alkali exciter (a mixed solution of water glass and sodium hydroxide) for mixing and preparation, and contacting the sludge through efficient stirring to form a solid waste-based early-strength curing agent. , reduce the amount of alkali triggering agent, and improve the curing stability and strength of the sludge.

Benefits of technology

The green and low-carbon recycling of sludge curing agents is achieved, energy consumption is reduced, the post-curing strength and stability of sludge are significantly improved, the heavy metal leaching liquid content that meets industry standards is also avoided waste of land resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005033886830000061
    Figure BDA0005033886830000061
  • Figure BDA0005033886830000062
    Figure BDA0005033886830000062
  • Figure BDA0005033886830000071
    Figure BDA0005033886830000071
Patent Text Reader

Abstract

The invention relates to the technical field of curing treatment, and discloses a solid-waste-based early-strength curing agent and a preparation method thereof.The solid-waste-based early-strength curing agent is prepared from, by weight, 41.03% of slag powder, 20.51% of fly ash, 15.38% of carbide slag and 23.08% of alkali activator; sludge is taken as a curing object, the mass of wet sludge is taken as a reference, the initial water content of the wet sludge is 60%-70%, and the mixing amount of a curing agent in percentage by mass is 10%-50%; the alkali activator is a mixed solution of water glass and sodium hydroxide solid, wherein the mass ratio of the water glass to the sodium hydroxide solid is 5-5.2; the baume degree of water glass in the alkali activator is 38, the modulus is 3.2, and the density is 1.360 g / cm. According to the solid-waste-based early-strength curing agent and the preparation method thereof, the slag powder, the fly ash and the carbide slag are mixed to prepare the curing agent, a large amount of solid waste is used, and the solid waste is effectively utilized for cyclic utilization, so that the concepts of circular economy and green development are practiced, and the energy consumption is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solidification treatment, in particular to a solid waste-based early-strength curing agent and a preparation method thereof. Background Art

[0002] At present, sanitary landfill is a more practical way to dispose of sludge in a centralized manner. However, due to the special properties of the sludge such as high water content, more harmful substances, and foul odor, the soil in the sludge pond and the surrounding area is very soft and has extremely poor bearing capacity, which not only seriously affects the subsequent use of the landfill, but also has an adverse impact on the surrounding environment. The existing sludge solidification technology is to transfer the curing agent in the storage bin through a high-pressure pipeline to the rapid mixing equipment in the sludge pond to achieve rapid mixing with the sludge, thereby achieving sludge solidification and stabilization. However, the mixing and mixing device achieves sludge solidification and stabilization by adding a curing agent. At present, the main raw materials of the sludge curing agent are cement, and the auxiliary materials are lime, bentonite, and high-alkaline ore. Some curing agents will add ferrous sulfate, sodium silicate and other additives. However, the use of this curing agent has some defects, such as:

[0003] At present, the technology of solidifying sludge pays more attention to its environmental indicators and has lower strength requirements. However, in order to ensure the subsequent safe use of the landfill, the strength of the solidified sludge cannot be too low. In addition, the use of a large amount of cement will cause great energy consumption, and low-dosage cement curing agent cannot guarantee a good solidification effect, because the solidification efficiency release cycle of the combination of sludge and traditional cement system is short.

[0004] In view of the above problems, it is urgent to carry out innovative design based on the original sludge solidifying agent. Summary of the invention

[0005] The purpose of the present invention is to provide a solid waste-based early-strength curing agent and a preparation method thereof, so as to solve the problem proposed in the above background technology that using a large amount of cement to solidify sludge will cause great energy consumption, while a low-dosage cement curing agent cannot guarantee a good curing effect, and the curing efficiency release cycle of the combination of sludge and traditional cement system is short.

[0006] To achieve the above object, the present invention provides the following technical solution: a solid waste-based early-strength curing agent and a preparation method thereof, comprising the following components in weight fractions:

[0007] The curing agent includes: slag powder 41.03%, fly ash 20.51%, carbide slag 15.38%, alkali activator 23.08%;

[0008] Based on the mass of wet sludge, the initial moisture content of wet sludge is 60%-70%, and the mass percentage of curing agent is 10%-50%;

[0009] The alkaline activator is a mixed solution of water glass and sodium hydroxide solid, wherein the mass ratio of water glass to sodium hydroxide solid is 5 to 5.2;

[0010] The Baume degree, modulus and density of the water glass in the alkaline activator are 38 and 3.2 respectively.

[0011] The sodium hydroxide solid purity is greater than or equal to 96%;

[0012] The specific surface areas of the granulated blast furnace slag powder, fly ash and carbide slag are not less than 400 m2 / kg.

[0013] The adoption of the above technical solution makes it easy to reduce the production of alkali activators in sludge solidifying agents and improve green development.

[0014] Preferably, the slag powder has a density greater than or equal to 2.8 g / cm 3 , activity index 7d not less than 70%, 28d not less than 95%, fluidity ratio greater than or equal to 95%, initial setting time ratio less than or equal to 200%.

[0015] The above technical solution is used to screen the quality of slag powder and to perform preparation while improving the quality of slag powder.

[0016] Preferably, the slag powder has the following mass fractions: water content not more than 1%, sulfur trioxide not more than 4%, chloride ion not more than 0.06%, loss on ignition not more than 1%, and insoluble matter not more than 3%.

[0017] The above technical solution is adopted to improve the quality of sludge solidifying agent by limiting the standard of slag powder.

[0018] Preferably, the fly ash has a 45 μm square mesh sieve residue of no more than 12%, a water storage ratio of no more than 95%, a strength activity index of no less than 70% at 7d and no less than 80% at 28d.

[0019] The above technical solution is used to screen the quality of fly ash and to perform preparation while improving the quality of fly ash.

[0020] Preferably, the fly ash has a loss on ignition of no more than 5%, a water content of no more than 1%, a sulfur trioxide content of no more than 3.5%, and a free calcium oxide content of no more than 1.0%.

[0021] By adopting the above technical solution, the quality of solidifying agent preparation can be improved by controlling the quality and grade of fly ash.

[0022] A method for preparing a solid waste-based early-strength curing agent, which is used in the production of the above-mentioned curing agent, is characterized in that it comprises the following steps:

[0023] S1. Prepare an alkali activator according to the ratio of water glass and solid sodium hydroxide, slowly pour solid sodium hydroxide into the water glass liquid in batches, stirring continuously at low speed during the period, until all the sodium hydroxide is poured, continue stirring for 5-10 minutes and let stand until the alkali activator is no longer exothermic;

[0024] S2. According to the above slag powder, fly ash and carbide slag ratio, the granulated blast furnace slag, fly ash and carbide slag are put into the mixing equipment for full mixing;

[0025] S3. Add the products prepared in S1 and S2 into the sludge at the same time, stir them to fully contact and fuse with the sludge, and solidify the sludge.

[0026] The above technical solution is adopted to fully prepare the sludge solidifying agent and contact it with the sludge for production treatment.

[0027] Preferably, during the stirring process of pouring the water glass and sodium hydroxide solid in the alkaline activator in step S1 in batches, it is necessary to wait for the sodium hydroxide solid to be fully fused without residue.

[0028] By adopting the technical solution, water glass and sodium hydroxide solid are fully fused to form an alkali activator.

[0029] Preferably, in step S3, the mixture of the alkali activator and the slag powder, fly ash and carbide slag is stirred and mixed synchronously with the sludge during the mixing process, so that the sludge is fully in contact with the alkali activator, the slag powder, fly ash and carbide slag.

[0030] The adoption of the above technical solution facilitates the reaction between the solidifying agent and the sludge, thereby increasing the solidification stability of the sludge.

[0031] Compared with the prior art, the present invention has the following beneficial effects: the solid waste-based early-strength curing agent and its preparation method:

[0032] 1. By mixing slag powder, fly ash and carbide slag, a large amount of solid waste is used and solid waste is effectively recycled, thus practicing the concept of circular economy and green development. Since the amount of alkali activator in the curing agent is low, energy consumption is reduced, making the use of the curing agent more green and low-carbon;

[0033] 2. By efficiently stirring and mixing the sludge during the mixing process of slag powder, fly ash, carbide slag and alkali activator, the sludge is fully exposed to the alkali activator, slag powder, fly ash and carbide slag, and solidifies after standing. The heavy metal content of the sludge leachate after solidification meets the industry standard, and the volume of the sludge after solidification does not increase significantly, thereby achieving a relatively small volume increase of the solidified sludge, less land occupation of the solidified sludge, and avoiding waste of land resources in the landfill area;

[0034] 3. By fully mixing the sludge and the curing agent and waiting for curing, the sludge can have a certain strength in a short time after curing, and can significantly reduce the moisture content of the sludge. Through the alkali-induced reaction of the gelling system, the curing efficiency release cycle is longer than that of the traditional cement system, and the later strength of the sludge after curing is high. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] The present invention provides a technical solution: a solid waste-based early-strength curing agent and a preparation method thereof, comprising the following curing agent curing sludge construction steps:

[0037] S1. Prepare an alkali activator and a mixed fly ash, slag and carbide slag body according to the ratio;

[0038] S2. Stir the sludge thoroughly to make the water in the sludge evenly distributed, then put the slag powder, fly ash, carbide slag mixture and alkali activator mixed in S1 into the sludge and stir at high speed, and fully mix the curing agent and the sludge:

[0039] S3. The mixed sludge is gradually solidified after being left to stand. The solidification effect is obvious after the sludge is left to stand for 12 hours. As time goes by, the solidification effect gradually increases.

[0040] The properties of the sludge in the above construction step S3 are shown in the following table:

[0041] Soil particle density Plastic limit\% Liquid limit\% Moisture content\% Organic matter\% 1.67 23.9 69.2 65.2 31.34

[0042] Example

[0043] The curing agent includes the following components by weight: 41.03% of S95 slag powder, 20.51% of fly ash, 15.38% of carbide slag, and 23.08% of alkali activator. Based on the mass of wet sludge, the mass percentage of the curing agent in the above ratio is 40%;

[0044] After the curing agent and sludge are fully mixed, they are placed into a 70.7 mm cubic test mold and demoulded after 24-48 hours.

[0045] The sludge solids produced in the embodiment are cured to the designed age and then subjected to compression test, moisture content test and heavy metal leaching test;

[0046] The specific testing reference standards are:

[0047] (1) Cube compressive strength: After the specimen is made, it should be left at room temperature of 15-25℃ for 22-26 hours;

[0048] When the temperature is low, the time can be appropriately extended, but should not exceed two days and nights;

[0049] After the test pieces are made, they should be numbered and demoulded immediately;

[0050] After demoulding, the specimens should be immediately placed in a standard curing room with a temperature of 18-22°C and a relative humidity of more than 90% for curing;

[0051] After the specimen is taken out of the standard curing room, it should be tested in time. Before the test, the surface of the specimen needs to be wiped clean, the size is measured, and its appearance is checked. The pressure-bearing area of ​​the specimen is calculated. If the difference between the measured size and the nominal size does not exceed 1mm, the nominal size can be used for calculation;

[0052] Place the test piece on the surface of the lower pressure plate or lower pad of the testing machine. The pressure-bearing surface of the test piece should be perpendicular to the top surface during molding, and the center of the test piece should be aligned with the center of the lower pressure plate or lower pad of the testing machine;

[0053] Start the testing machine, and when the upper pressure plate is close to the surface of the test piece or the upper pad, adjust the ball seat so that the contact surface is evenly compressed;

[0054] The pressure test should be loaded continuously and evenly, and the loading speed should be 0.2kN~1.5kN per second;

[0055] When the specimen is close to failure and the deformation speed increases, the throttle adjustment of the testing machine should be stopped until the specimen fails. Record the maximum load with an accuracy of 0.1MPa.

[0056] (2) Moisture content test: clean the inorganic matter on the surface of the sample and put it into a sealed container;

[0057] Use a constant-weight evaporating dish to weigh about 20 g of the evenly crushed sludge sample, and weigh the sample accurately to 0.001 g, which is recorded as M;

[0058] Then use the following formula to calculate:

[0059] W=[M-(m2-m1)]\M×100%

[0060] W: sample moisture content, unit %;

[0061] M: weigh the mass of the sludge sample, in g;

[0062] m2: the mass of the sludge sample after constant weight is added to the evaporating dish, in g;

[0063] m1: Mass of the empty evaporating dish after constant weight, in g.

[0064] (3) Detection of heavy metal leaching concentration in sludge: The leaching toxicity test of the collected samples was carried out using the sulfuric acid and nitric acid method, and the experimental data results were compared with GB5085.3-2007 "Identification of Hazardous Waste Identification Standards for Leaching Toxicity".

[0065] (4) The volume increase ratio is calculated using the following formula:

[0066]

[0067] The solidified sludge volume expansion ratio of this embodiment is 1.35, the 7d moisture content is 29.88%, the 7d compressive strength is 1011.87 kPa, and the 28d compressive strength is 2317.18 kPa, which far meets the requirements of GBT23485-2009 "Mud for mixed landfill of sludge from urban sewage treatment plants".

[0068] The heavy metal leaching concentrations of the original sludge and the 7d and 28d solidified sludge in this example are shown in the following table:

[0069]

[0070] It can be seen that the solidifying agent has a good solidifying effect on the heavy metal ions in the sludge, and the heavy metal content of the sludge leachate after solidification meets the requirements of GB5085.3-2007 "Identification Standard for Hazardous Waste Leaching Toxicity Identification";

[0071] The curing agent ratio of the embodiment is obtained by adopting orthogonal test design to obtain the corresponding test results, wherein the fly ash, slag, and carbide slag dosage is based on the mass of wet sludge, and the alkali activator dosage is based on the mass and the sum of the fly ash, slag, and carbide slag, and the data are shown in the following table:

[0072]

[0073] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A solid waste-based early-strength curing agent, characterized in that: The components include the following ingredients by weight: The curing agent includes: slag powder 41.03%, fly ash 20.51%, carbide slag 15.38%, alkali activator 23.08%; Based on the mass of wet sludge, the initial moisture content of wet sludge is 60%-70%, and the mass percentage of curing agent is 10%-50%; The alkaline activator is a mixed solution of water glass and sodium hydroxide solid, wherein the mass ratio of water glass to sodium hydroxide solid is 5 to 5.2; The Baume degree, modulus and density of the water glass in the alkaline activator are 38 and 3.2 respectively. The sodium hydroxide solid purity is greater than or equal to 96%; The specific surface areas of the granulated blast furnace slag powder, fly ash and carbide slag are not less than 400 m2 / kg.

2. A solid waste-based early-strength curing agent according to claim 1, characterized in that: The slag powder reaches a density greater than or equal to 2.8 g / cm 3 , activity index 7d not less than 70%, 28d not less than 95%, fluidity ratio greater than or equal to 95%, initial setting time ratio less than or equal to 200%.

3. A solid waste-based early-strength curing agent according to claim 1, characterized in that: The slag powder has the following mass fractions: water content not more than 1%, sulfur trioxide not more than 4%, chloride ion not more than 0.06%, loss on ignition not more than 1%, and insoluble matter not more than 3%.

4. The solid waste-based early-strength curing agent according to claim 1, characterized in that: The fly ash has a 45μm square mesh sieve residue fineness of no more than 12%, a water storage ratio of no more than 95%, a strength activity index of no less than 70% at 7d and no less than 80% at 28d.

5. The solid waste-based early-strength curing agent according to claim 1, characterized in that: The fly ash has a loss on ignition of no more than 5%, a water content of no more than 1%, a sulfur trioxide content of no more than 3.5%, and a free calcium oxide content of no more than 1.0%.

6. A method for preparing a solid waste-based early-strength curing agent, used in the production of the curing agent of claim 1, characterized in that: The following steps are involved: S1. Prepare an alkali activator according to the ratio of water glass and solid sodium hydroxide, slowly pour solid sodium hydroxide into the water glass liquid in batches, stirring continuously at low speed during the period, until all the sodium hydroxide is poured, continue stirring for 5-10 minutes and let stand until the alkali activator is no longer exothermic; S2. According to the above slag powder, fly ash and carbide slag ratio, the granulated blast furnace slag, fly ash and carbide slag are put into the mixing equipment for full mixing; S3. Add the products prepared in S1 and S2 into the sludge at the same time, stir them to fully contact and fuse with the sludge, and solidify the sludge.

7. The method for preparing a solid waste-based early-strength curing agent according to claim 6, characterized in that: In the stirring process of pouring the water glass and sodium hydroxide solid in the alkali activator in step S1 in batches, it is necessary to wait for the sodium hydroxide solid to be fully fused without residue.

8. The method for preparing a solid waste-based early-strength curing agent according to claim 6, characterized in that: In the step S3, the mixture of the alkali activator and the slag powder, fly ash and carbide slag is stirred and mixed synchronously with the sludge during the mixing process, so that the sludge is fully in contact with the alkali activator, the slag powder, the fly ash and the carbide slag.

9. According to the proposed curing principle of the curing agent, the present invention is not only applicable to sludge, but also has application prospects in the field of curing and improving soft soil, weak soil, silt and loess.